2019
DOI: 10.1111/jace.16540
|View full text |Cite
|
Sign up to set email alerts
|

Predicting properties of MgO·nAl2O3 by first‐principles calculation combined with bond valence models

Abstract: Spinel‐type oxides have attracted tremendous attentions owing to their wide applications. However, the complicated composition and structure of spinel‐type solid solution brought about challenge to explore the relationship among composition, structure, and properties. A new approach which combined first‐principles calculation with bond valence models was developed to explore the composition dependence of structure and properties for spinel‐type oxide solid solution. The first‐principles calculation was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…The variation of the derived Poisson's ratio is shown in Figure 4B as well. With the rise of n , ZnO· n Al 2 O 3 shows some improvement in elastic moduli ( B , G , and E ), and essentially constant Poisson's ratio, which is similar to MgO· n Al 2 O 3 8,19 …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The variation of the derived Poisson's ratio is shown in Figure 4B as well. With the rise of n , ZnO· n Al 2 O 3 shows some improvement in elastic moduli ( B , G , and E ), and essentially constant Poisson's ratio, which is similar to MgO· n Al 2 O 3 8,19 …”
Section: Resultsmentioning
confidence: 77%
“…Hence, results based on the crystal structure parameters determined from LDA, that is, by Equations () and () and those from GGA, that is, by Equations () and () can be seen as the extremes of properties, respectively. The reliability of the reconstructed structure was assessed by the bond valence arguments 19 (Seen in Supporting Information ). In this work, the global instability index ( GII ) for the reconstructed structure of ZnO· n Al 2 O 3 ( n = 1–4) from either LDA or GGA is lower than 0.20 (inset in the bottom left of Figure 2), suggesting the structural stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the site preference of disordered species should be fully understood first, because the distribution of cationic vacancies and inversion atoms is not totally random. 39,40 The calculation is relatively time-consuming and inefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the thermal expansion of RE 2 Si 2 O 7 is mainly controlled by the interaction between O atoms and surrounding RE atoms, and the vibration of Si–O–Si is significant for the thermal expansion of RE 2 Si 2 O 7 . More recently, a new approach that combines first‐principles calculations and bond valence models (FP‐BVM) was developed for exploring the origin of composition‐dependent properties in complex systems 19–21 . The successful applications of FP‐BVM in complex spinel‐type compounds 19–21 bring enlightenment to MgAlON solid solution.…”
Section: Introductionmentioning
confidence: 99%